Diseño e implementación de un tratamiento físico biológico demostrativo para la depuración de las aguas residuales provenientes de la porcicultura, en la finca de la familia sarango condolo, ubicada en el barrio santa bárbara, cantón Centinela del Cóndor - Sarango Condolo, Darwin Gabriel (2016)
The present research was carried out at the Sarango Condolo family farm, “Santa Bárbara” neighborhood, from “Centinela del Cóndor” town, the purpose was to design and implement a biological and physical demonstrative treatment referable and replicable, for the sewage water treatment from the porci-culture through artificial wetlands alternative, sustainable, and low-cost to reduce pollution of the Santa Bárbara canyon. The development of the project consisted first to carry out a socioeconomic characterization of the activity and to determine the grade of pollution of the sewage water of the porci-culture, through a laboratory analysis of the physical, chemical and microbiological characteristics, after, it was determined the sewage water flow which is generated daily through the volumetric method, then through design parameters, the physical-biological treatment dimensions were determined and using the AUTOCAD program , the design of the box retention solids was designed, sedimentation tank, artificial-superficial wetland with Eichornia crassipes, and horizontal subsurface flow wetland with biological filter and Echinochloa polystachya, which were built of concrete with brick walls. Finally, to determine the removal efficiency of the pollutants from the treatment, a sample of treated sewage water was collected, and a laboratory analysis was developed achieving a reduction of total solids (45%), suspended solids (83%), total phosphorus (82%), total nitrogen (92%), biochemical demand for oxygen (DBO5), chemical oxygen demand (DQO) (90%) and fecal coliforms (93%). Keywords: Physical / biological treatment, porci-culture